Possible DRESS Syndrome in a Patient with Systemic Sclerosis and Rheumatoid Arthritis during Treatment with Lamotrigine: A Case Report - Ivan Jeremic (Highlights on Medicine and Medical Research Vol. 4, 2021)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome is a severe, potentially life-threatening idiosyncratic drug reaction. It is usually caused by antiepileptics, antibiotics or non-steroidal anti-inflammatory drugs, after a latency period of three weeks to three months. Typical clinical features include mucocutaneous rash, fever, lymphadenopathy and internal organ involvement. We report a patient with systemic sclerosis, rheumatoid arthritis and osteoporosis who developed possible DRESS syndrome to lamotrigine, used for epilepsy. Clinical features suggesting DRESS syndrome included severe rash, fever, hematological abnormalities and time of appearing and disappearing of skin changes. The condition was initially unsuccessfully treated as an acute allergic reaction to ibandronate, without discontinuation of lamotrigine. This report aims to increase the awareness of this rare entity in the rheumatology community.